2009
DOI: 10.1111/j.1365-246x.2009.04385.x
|View full text |Cite
|
Sign up to set email alerts
|

Depth extent of damage zones around the central Calaveras fault from waveform analysis of repeating earthquakes

Abstract: S U M M A R YWe systematically investigate spatial variations of temporal changes and depth extent of damage zones along the Calaveras fault that ruptured during the 1984 Morgan Hill earthquake by the waveform analysis of 333 sets of repeating earthquakes. We use a sliding window waveform cross-correlation technique to measure traveltime changes in waveforms generated by each repeating cluster. We find clear traveltime delays in the S-and early S-coda waves for events immediately after the Morgan Hill main sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 85 publications
(232 reference statements)
4
21
0
Order By: Relevance
“…The overall geometry of the ‘flower‐like’ damage zones in our simulations is compatible with field observations (e.g. Sylvester 1988; Rockwell & Ben‐Zion 2007; Zhao & Peng 2009) and with numerical simulations of off‐fault deformation (e.g. Ma 2008).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The overall geometry of the ‘flower‐like’ damage zones in our simulations is compatible with field observations (e.g. Sylvester 1988; Rockwell & Ben‐Zion 2007; Zhao & Peng 2009) and with numerical simulations of off‐fault deformation (e.g. Ma 2008).…”
Section: Resultssupporting
confidence: 84%
“…Karabulut & Bouchon 2007; Wu et al . 2009; Zhao & Peng 2009). To update the constraints on healing parameters we use recent fault zone observations from the ECSZ (Cochran et al .…”
Section: Damage Rheology Healing Formulation and Modelling Approachmentioning
confidence: 99%
“…We identify a pair of earthquakes as CREs if both the cross‐correlation coefficient and the phase coherency are greater than 0.95, for at least two stations (Figure ), to reduce the chance of false CRE detections. Our cross‐correlation and coherency thresholds are comparable to those used in previous studies [ Zhao and Peng , ; Shirzaei et al ., ; Turner et al ., ]. Two seismograms that exceed these thresholds are identified as pairs of repeating earthquakes.…”
Section: Data and Analysismentioning
confidence: 99%
“…Previous studies have identified repeating earthquakes in a large variety of tectonic environments including California [ Vidale et al , ] Japan [ Uchida et al , ; Matsuzawa et al , ; Kimura et al , ], China [ Schaff and Richards , ], Taiwan [ Chen et al , , ], Turkey [ Peng and Ben‐Zion , ], and Tonga‐Vanuatu [ Yu , ]. Here repeating earthquakes have been observed along the creeping segment of the San Andreas Fault [ Nadeau and Johnson , ; Schaff et al , ; Rubin et al , ; Taira et al , ] and along the Calaveras fault [ Vidale et al , ; Marone et al , ; Schaff and Beroza , ; Peng et al , ; Zhao and Peng , ; Templeton et al , ]. Characteristic repeating sequences in these environments have been exploited as a common framework to explore the physical mechanism behind their origin and occurrence [ Sammis and Rice , ; Beeler et al , ].…”
Section: Introductionmentioning
confidence: 99%